PENERAPAN BAHAN AJAR BERBASIS POTENSI LOKAL EKOSISTEM MANGROVE PONDOK BALI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF - siti sriyati; Wahyu Rimbun; Amprasto Amprasto (EDUSAINS, 2019)
IMPROVEMENT OF CREATIVE THINKING BY TEACHING MATERIALS BASED ON LOCAL POTENTIAL OF PONDOK BALI MANGROVE AbstractThe mangrove ecosystem of Pondok Bali in Subang can be used as a learning resource in the form of contextual teaching materials for students around it. This study aims to apply teaching materials based on the local potential of Pondok Bali Subang mangrove ecosystem to improve students' creative thinking skills. This study uses a pre-experimental design method. The research subjects were class XI Fisheries Department with a total of 17 students.The instruments in the study included teaching materials based on the local potential of mangrove ecosystems, questions of creative thinking and student response questionnaires. Teaching materials based on local potential mangrove ecosystems were developed first and tested for their feasibility and readability before being used by students. Teaching materials are equipped with practice questions that explore students' creative thinking abilities. The results showed an increase in students' creative thinking skills before and after the application of teaching materials was applied. N-gain values of the indicators of creative thinking are consecutive: fluency, flexibility, originality and elaboration are 0.41, 0.54, 0.44 and 0.55 which are in the medium category. The increase in N-gain is: 23.5% of students in the high category, 58.8% in the medium category, 11.8% in the low category and 5.9% in no increase. Student responses to teaching materials showed a positive response (93.9%). AbstrakEkosistem mangrove Pondok Bali di Subang dapat dijadikan sumber belajar dalam bentuk bahan ajar yang kontektual bagi siswa-siswa di sekitarnya. Penelitian ini bertujuan untuk menerapkan bahan ajar berbasis potensi lokal ekosistem mangrove Pondok Bali  Subang untuk meningkatkan kemampuan berpikir kreatif siswa. Penelitian ini menggunakan metode pre-experimental design. Subjek penelitian adalah siswa kelas XI Jurusan Perikanan dengan  jumlah siswa sebanyak 17 orang. Instrumen pada penelitian meliputi bahan ajar berbasis potensi lokal ekosistem mangrove, soal berpikir kreatif dan angket respon siswa. Bahan ajar berbasis potensi lokal ekosistem mangrove disusun terlebih dahulu dan diuji kelayakan serta keterbacaannya sebelum digunakan oleh siswa. Bahan ajar dilengkapi dengan pertanyaan-pertanyaan latihan yang menggali kemampuan berpikir kreatif siswa. Hasil penelitian menunjukkan terjadi peningkatan kemampuan berpikir kreatif siswa sebelum dan sesudah diterapkan bahan ajar.  Berturut-turut nilai N-gain dari indikator berpikir kreatif:  fluency, flexibility, originality dan elaboration  adalah 0,41, 0,54, 0,44 dan 0,55 yang termasuk kategori sedang. Peningkatan N-gainnya adalah: 23,5% siswa berkategori tinggi, 58,8%  berkategori sedang,  11,8% berkategori rendah dan 5,9% tidak mengalami peningkatan. Tanggapan siswa terhadap bahan ajar menunjukkan respon yang positif (93,9%).